Предмет: Алгебра,
автор: Аноним
3) -16 + (4 + 2) = x(x + 12)
Ответы
Автор ответа:
1
3) -16 + (4 + 2) = x(x + 12)
-16+6=x^2+12x
-10=x^2+12x
-x^2-12x-10=0
X^2+12x+10=0
X1=-6-в корне 26
Х2=-6+в корне 26
-16+6=x^2+12x
-10=x^2+12x
-x^2-12x-10=0
X^2+12x+10=0
X1=-6-в корне 26
Х2=-6+в корне 26
Автор ответа:
2
Ответ:
Объяснение:
-16 + (4 + 2) = x(x + 12)
-16+6=x²+12x
x²+12x+10=0
Δ=144-40=104 ; √Δ=√104=2√26
x1=(-12-2√26)/2=-6-√26
x2=(-12+2√26)/2=-6+√26
Похожие вопросы
Предмет: Геометрия,
автор: KristinaJapan
Предмет: Українська мова,
автор: alexpro954
Предмет: Алгебра,
автор: LenaMurena
Предмет: Информатика,
автор: CKyTepucT
Предмет: Алгебра,
автор: MarioCascas